(untitled) (Itinera, 2016)
Endgame (1957), considered by many as Samuel Beckett’s major work, stands out as a “terminal” play, a play in which the characters live in an absolute present, devoid of any idea of future and completely disconnected from the world of memories, which are so far away as to seem mere hallucinations. How, then, should these characters live in a universe that is so close to its end? By waiting, Beckett suggests; by waiting, paradoxically, for things to take their own course.